Usability of Context-Aware Mobile Educational Game - Ching-Wen Chen; Echo Huang; Kinshuk; Maiga Chang; Chris Lu (Knowledge Management & E-Learning: An International Journal, 2011)
Ubiquitous learning is an innovative approach that combines mobile learning and context-awareness, can be seen as kind of location-based services, first detects user’s location, knows surrounding context, and gets learning profile, and then provides the user learning materials accordingly. Game-based learning have become an emerging research topic and been proved that can increase users’ motivations and interests. The aim of our research is to present a context-awareness multi-agent-based mobile educational game that can generate a series of learning activities for users doing On-the-Job training and make users interact with specific objects in their working environment. We reveal multi-agent architecture (MAA) into the mobile educational game design to achieve the goals of developing a lightweight, flexible, and scalable game on the platform with limited resources such as mobile phones. A scenario with several workplaces, research space, meeting rooms, and a variety of items and devices in 11th floor of a university’s building is used to demonstrate the idea and mechanism proposed by this research. At the end, a questionnaire is used to examine the usability of the proposed game. 37 freshmen participate in this pilot study and the results show that they are interested in using the game and the game does help them getting familiar with the new environment.